Urinary cadmium and lead concentrations and their relation to blood pressure in a population with low exposure. Issue 2 (May 1984) - Staessen, J; Bulpitt, C J; Roels, H; Bernard, A; Fagard, R; Joossens, J V; Lauwerys, R; Lijnen, P; Amery, A
Abstract : The 24 hour urinary excretion of cadmium (U-Cd) and lead (U-Pb), and the excretion of beta-2- microglobulins and retinol binding protein concentration in spot urines, were determined in a random 4% sample of the population of a small Belgian town. Blood pressure and body weight were measured on two separate occasions. U-Cd averaged 2.4 nmol/24 h in 46 youths, increased with age, and was significantly higher in 57 adult men as compared with 59 women (9.3 v 7.2 nmol/24 h; p less than 0.01). U-Pb averaged 28 nmol/24 h in youths and similarly increased with age: adult men excreted more lead than women (64 v 40.0 nmol/24 h; p less than 0.001). Among men, manual workers excreted more cadmium (12.6 v 7.5 nmol/24 h; p less than 0.05) but a similar amount of lead (62 v 61 nmol/24 h) compared with office workers. After adjusting for sex and age, U-Cd and U-Pb were not related to body weight and cigarette consumption. In simple regression analysis, U-Cd was positively correlated with both systolic (r = +0.30; p less than 0.05) and diastolic (r = +0.38; p less than 0.01) blood pressure in women. After adjusting for other contributing variables, however, a weak but negative relation became apparent between systolic pressure and U-Cd in women (t = -2.21; p = 0.033) and between diastolic pressure and U-Cd in men (t = -2.04; p = 0.047). In women urinary beta-2-microglobulin was related to diastolic pressure (r-0.44; p<0.01) and after adjusting for age to both systolic (t=2.75; p=0.009) and diastolic (t=-3.07; p=0.004) pressure. In none of the sex-age groups did U-Pb and retinol binding protein contribute to the blood pressure variability.